Hemodynamic changes in the right ventrolateral prefrontal cortex relate to the psychological mood profile. (29th May 2022) - Tsuchiya, Kenji; Shimoda, Kaori; Mitsui, Shinichi; Yamaya, Noriki; Kikuchi, Senichiro; Fujita, Takaaki; Tozato, Fusae
Highlights: fNIRS measured the prefrontal cortex activity during a cleaning task. The cleaning task increased oxy-Hb signals in the bilateral VLPFC and right FP. The right VLPFC signal was negatively correlated with Confusion-Bewilderment score. Abstract: Previous reports indicate that the right ventrolateral prefrontal cortex (VLPFC) is involved in emotional regulation. However, most such studies were performed under unphysiological conditions, like the administration of transcranial direct current or repetitive transcranial magnetic stimulation. We have shown that the right VLPFC is stimulated by an acute bout of daily activity, such as cleaning. Here, we investigated the relationship between the right VLPFC and mood changes using this system. Fourteen young adults vacuumed a floor as a cleaning task and kept a standing position as a control task on separate days. The oxyhemoglobin (oxy-Hb) and deoxy-hemoglobin (deoxy-Hb) signals of the prefrontal cortex were measured during the tasks. The mood scale scores of Profile of Mood States 2nd edition (POMS) and Two-Dimensional Mood Scale (TDMS) were measured before and after both tasks. The differences in subscale scores between pre- and post-tasks in both scales were calculated as ΔPOMS and ΔTDMS. The cleaning task significantly increased the oxy-Hb signal in the bilateral VLPFC and right frontopolar, but did not affect the deoxy-Hb signals. The control task significantly decreased the oxy-Hb signal in some brain regions. The Confusion–Bewilderment score in POMS changed after the cleaning task. Importantly, the oxy-Hb signal in the right VLPFC was negatively correlated with the ΔPOMS Confusion–Bewilderment score. The activity of the right VLPFC stimulated by the cleaning task might have a correlation with the Confusion–Bewilderment mood state.